A Validation Study of the Icelandic Version of the Marlowe-Crowne Social Desirability Scale - Erna Karólína Arnardóttir 1989- (2013)
The effect of social desirability, or the tendency to give answers that will make the best impression of the respondent, is one of the most studied response biases in psychology. A wide variety of scales has been constructed to assess the impact of social desirability, one of which is the Marlowe-Crowne Social Desirability Scale (MCSD). Since it was already available in Icelandic, the aim of this study was to test whether the Icelandic version of the MCSD was a valid measure of social desirability influences. To test this, the relationships were examined between those scoring high on MCSD and those who were playing the cheap-talk game either under a name or anonymously. It was hypothesized that if MCSD measures social desirability, individuals needing approval (scoring high on MCSD) and playing the cheap-talk game under their names should lie less than those playing the game anonymously. A total of 156 first-year students at Reykjavík University participated. They were randomly divided into two groups: those who would play the cheap-talk game under their names and those who would remain anonymous. The research took place in a computer lab where the students first answered the MCSD and then played the cheap-talk game. An examination of the data showed significant difference between the experimental and control groups upon enrolling in the study. For this unfortunate reason, the researcher was unable to test any hypothesis or draw any conclusions reliably. Therefore, it will be necessary to repeat the study. Félagslegur æskileiki, tilhneigingin hjá einstaklingum til að gefa svör sem lætur þá líta vel út, er eitt af mest rannsökuðu svarskekkjum á sviði sálfræðinnar. Margir skalar hafa verið smíðaðir til að meta félagslegan æskileika. Einn þeirra er Marlowe-Crowne Social Desirability Scale (MCSD) og hefur hann verið þýddur á íslensku. Markmið rannsóknarinnar var að kanna hvort íslenska þýðingin á MCSD sé gild mæling á félagslegum æskileika. Til þess að ná þessu markmiði var sambandið skoðað á milli þeirra sem ...